Bloody nipple discharge in an infant - Ji Yeon Seo; Sang Jeong Kim; Soon Joo Lee; Eun Song Song; Young Jong Woo; Young Youn Choi (Korean Pediatric Society, 2010)
Although milky nipple discharge appears frequently in infants, bloody nipple discharge is a very rare finding. We experienced a 4-month-old, breast-fed infant who showed bilateral bloody nipple discharge with no signs of infection, engorgement, or hypertrophy. The infant's hormonal examination and coagulation tests were normal, and an ultrasound examination revealed mammary duct ectasia. The symptoms resolved spontaneously within 6 weeks without any specific treatment, except that we advised the mother to refrain from taking herbal medicine. Since no such case has been previously reported in Korea, we present this case with a brief review of the literature.